Evolutionary and Deterministic Methods for Design Optimization and Control With Applications to Industrial and Societal Problems - Andrés-Pérez, Esther; González, Leo M.; Periaux, Jacques; Gauger, Nicolas; Quagliarella, Domenico; Giannakoglou, Kyriakos (Computational Methods in Applied Sciences, 2019)
This book contains thirty-five selected papers presented at the International Conference on Evolutionary and Deterministic Methods for Design, Optimization and Control with Applications to Industrial and Societal Problems (EUROGEN 2017). This was one of the Thematic Conferences of the European Community on Computational Methods in Applied Sciences (ECCOMAS). Topics treated in the various chapters reflect the state of the art in theoretical and numerical methods and tools for optimization, and engineering design and societal applications. The volume focuses particularly on intelligent systems for multidisciplinary design optimization (mdo) problems based on multi-hybridized software, adjoint-based and one-shot methods, uncertainty quantification and optimization, multidisciplinary design optimization, applications of game theory to industrial optimization problems, applications in structural and civil engineering optimum design and surrogate models based optimization methods in aerodynamic design.